Bridging Intimate Partner Violence and the Human Brain: A Literature Review. (January 2014) - Wong, Janet Yuen-Ha; Fong, Daniel Yee-Tak; Lai, Vincent; Tiwari, Agnes
Past studies mainly focused on the physical and structural brain injuries in women survivors with a history of intimate partner violence (IPV), but little attention has been given to the biological impact and cognitive dysfunction resulting from such psychological stress. In this article, we aim to establish the connection between IPV and the brain by reviewing current literature examining (1) the biological mechanisms linking IPV, stress, and the brain; (2) the functional and anatomical considerations of the brain in abused women; and (3) the abused women's behavioral responses to IPV, including fear, pain, and emotion regulation, by utilizing functional neuroimaging. The major significance of this study is in highlighting the need to advance beyond self-reports and to obtain scientific evidence of the neurological impact and cognitive dysfunction in abused women with a history of IPV, an area in which current literature remains at a descriptive level.